2020
DOI: 10.21608/epsj.2020.81033
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Carcass Characteristics and Meat Quality of Broiler Chickens at Different Marketing Ages

Abstract: Length of production cycle and broiler marketing decision is an important issue especially when productivity and product quality are considered. The objectives of this study were to determine the effects of the age at marketing on productive performance, carcass characteristics and meat quality traits of broiler chickens at five different ages. For this purpose, a total of 450 mixed-sex Cobb 500 broiler chicks were used. Chicks were randomly distributed into five equal groups with 3 replicates allocated in 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 14 publications
(17 reference statements)
8
14
0
Order By: Relevance
“…The pH for the breast meat was significantly higher in the highest slaughter age group of 34 days compared to the other slaughter age groups (p < 0.05), and it also appeared to increase with lengthening the slaughter age for the thigh meat. A previous study reported an increasing pH level with increasing slaughter age for broilers from 30 to 50 days [25], similar to other poultry meat, which was consistent with this study. Changes in meat pH of slaughter age are concomitant with changes in lactate and glycolytic potential [26].…”
Section: Ph and Colorsupporting
confidence: 93%
“…The pH for the breast meat was significantly higher in the highest slaughter age group of 34 days compared to the other slaughter age groups (p < 0.05), and it also appeared to increase with lengthening the slaughter age for the thigh meat. A previous study reported an increasing pH level with increasing slaughter age for broilers from 30 to 50 days [25], similar to other poultry meat, which was consistent with this study. Changes in meat pH of slaughter age are concomitant with changes in lactate and glycolytic potential [26].…”
Section: Ph and Colorsupporting
confidence: 93%
“…According to a recent study of the characteristics of broiler carcasses, among the various changes in the proximate composition, the protein content tended to increase with increasing marketing age, with a higher protein content being found in the 34 day sample than in the 28 day sample, as also observed herein [ 3 ]. Such differences in protein content according to age were also consistent with the results of carcass characteristics analysis in the 30–50 day samples examined by Abougabla and Taboosha [ 20 ], who also reported that the protein content increased while the water content decreased. These results indicate that the differences in the proximate composition according to the marketing age would also affect the proximate composition of cured chicken breast.…”
Section: Resultssupporting
confidence: 89%
“…In general, the shear force of meat increases with age due to the fact that the protein content in the muscle increases relative to the other components, and the composition of the connective tissue becomes denser as the livestock matures [ 36 ]. Such densification of the muscle protein is caused by changes in the properties and collagen and elastin content, that is, the proteins of which the connective tissue is composed [ 20 ]. In the context of collagen, which has the most significant effect on reducing the protein’s tenderness upon maturation, the degree of crosslinking between the polypeptide chains increases, resulting in the formation of a more robust structure [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations